Wound Healing with Electrical Stimulation Technologies: A Review - Yt Jun Cheah (MDPI AG, 2021)
Electrical stimulation (ES) is an attractive field among clinicians in the topic of wound healing, which is common yet complicated and requires multidisciplinary approaches. The conventional dressing and skin graft showed no promise on complete wound closure. These urge the need for the exploration of electrical stimulation to supplement current wound care management. This review aims to provide an overview of electrical stimulation in wound healing. The mechanism of galvanotaxis related to wound repair will be reviewed at the cellular and molecular levels. Meanwhile, different modalities of externally applied electricity mimicking a physiologic electric field will be discussed and compared in vitro, in vivo, and clinically. With the emerging of tissue engineering and regenerative medicine, the integration of electroconductive biomaterials into modern miniaturised dressing is of interest and has become possible with the advancing understanding of smart biomaterials.